2017
DOI: 10.18203/2320-6012.ijrms20174672
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of left ventricular hypertrophy in patients of chronic kidney disease

Abstract: Background: Present study was conducted with an objective to study the prevalence of left ventricular hyper trophy (LVH) by echocardiography in patients with chronic kidney disease (CKD) and to find out correlation of left ventricular hypertrophy with severity of chronic kidney disease.Methods: From November 2012 to September 2014, 100 chronic kidney disease patients who were admitted in hospital or attended on OPD basis for dialysis were taken for study. Detailed history, clinical evaluation, laboratory inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…After LVH other most common abnormalities found on Echocardiography in CKD patients on haemodialysis were pericardial effusion and conduction abnormalities. 14 Behera BK et al, in a study found that Patients with CKD have LVH, which is more marked in patients with severe CKD. So, these patients should have a thorough cardiovascular evaluation even if there were no symptoms, and efforts should be made to prevent LVH, during the early course of renal insufficiency, such as strict control of hypertension, anaemia.…”
Section: Discussionmentioning
confidence: 97%
“…After LVH other most common abnormalities found on Echocardiography in CKD patients on haemodialysis were pericardial effusion and conduction abnormalities. 14 Behera BK et al, in a study found that Patients with CKD have LVH, which is more marked in patients with severe CKD. So, these patients should have a thorough cardiovascular evaluation even if there were no symptoms, and efforts should be made to prevent LVH, during the early course of renal insufficiency, such as strict control of hypertension, anaemia.…”
Section: Discussionmentioning
confidence: 97%